2019
DOI: 10.1075/hsld.8
|View full text |Cite
|
Sign up to set email alerts
|

Biscriptuality

Abstract: In the context of constantly increasing linguistic diversity in many parts of the world, opportunities and challenges arise for the acquisition of literacy skills. The successful development of literacy skills becomes a crucial prerequisite for educational attainment determining future career prospects of migrant students. Multilingual settings reveal the diversification of languages and scripts prompted in the context of migration. This monograph explores the phenomenon of biscriptuality and aims to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 207 publications
1
8
0
Order By: Relevance
“…The transcription of the reading test was conducted based on the Duden conventions for the transcription of Russian into German. The choice of this system is based on previous research indicating that Latin graphemes used in writing by German-Russian bilinguals show high correspondence with Duden conventions (Usanova, 2019), as these are written with Latin graphemes and are primarily based on reproduction of the sound (Mulisch, 1996).…”
Section: Instruments and Scoresmentioning
confidence: 99%
See 4 more Smart Citations
“…The transcription of the reading test was conducted based on the Duden conventions for the transcription of Russian into German. The choice of this system is based on previous research indicating that Latin graphemes used in writing by German-Russian bilinguals show high correspondence with Duden conventions (Usanova, 2019), as these are written with Latin graphemes and are primarily based on reproduction of the sound (Mulisch, 1996).…”
Section: Instruments and Scoresmentioning
confidence: 99%
“…Most studies conducted on literacy skills in bilinguals focus either on writing or on reading, with only a few focusing on both skills (e.g., Brehmer & Mehlhorn, 2018;Brehmer et al, in press;Dworin, 2003;2006;Klinger et al, 2019b;Sparrow et al, 2014). Studies conducted on writing in more than one language have shown that writing skills in different languages are positively interrelated (Schoonen et al, 2003;2011;Soltero-González et al, 2012;Sparrow et al, 2014;Uluçam-Wegmann et al, 2019;Usanova, 2019;. The studies which considered both skills in bilingual students revealed that the acquisition sequence for both skills may deviate from typical monolingual sequences (Dworin, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations